FORMATION OF FOREIGN LANGUAGE AND COMMUNICATION SKILLS IN PRIMARY SCHOOL PUPILS - Ruzmetova Novval Vakhabdzhanovna; Ramziddinova Xusnoraxon Xusniddin qizi (Bright Mind Publishing, 2026)
The article examines didactic and psycholinguistic foundations for developing foreign language and communication skills in primary school pupils. A mixed-method design was applied through classroom observations, diagnostic tasks, and comparative analysis. Findings indicate that communicative micro-tasks combined with formative assessment increases sustained oral participation, improves interaction quality, and supports early functional language use, contributing to a practical model for primary classrooms.
Keywords: Primary education, foreign language teaching, communicative competence, speech activity, formative assessment, classroom interaction, learning strategies.